If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 2(x + 5) = 12 + 5x Reorder the terms: 4x + 2(5 + x) = 12 + 5x 4x + (5 * 2 + x * 2) = 12 + 5x 4x + (10 + 2x) = 12 + 5x Reorder the terms: 10 + 4x + 2x = 12 + 5x Combine like terms: 4x + 2x = 6x 10 + 6x = 12 + 5x Solving 10 + 6x = 12 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 10 + 6x + -5x = 12 + 5x + -5x Combine like terms: 6x + -5x = 1x 10 + 1x = 12 + 5x + -5x Combine like terms: 5x + -5x = 0 10 + 1x = 12 + 0 10 + 1x = 12 Add '-10' to each side of the equation. 10 + -10 + 1x = 12 + -10 Combine like terms: 10 + -10 = 0 0 + 1x = 12 + -10 1x = 12 + -10 Combine like terms: 12 + -10 = 2 1x = 2 Divide each side by '1'. x = 2 Simplifying x = 2
| -4x+7(2x+15)=185 | | x^2+y^2-10x-12y=60 | | (u+5)*10=80 | | -2(S+-4)=0 | | 0.97+x=2.6 | | -0.5(11)+41.5= | | (q-4)*4=40 | | 49a^2+15a+16=0 | | -2/m=2 | | -5y-3=22 | | 18=-2(u-16)+16 | | X=116 | | 1X2/3= | | -2(-x-6)=14 | | 9m-1=m+11 | | 1/7(x-49)=5/7 | | 33-x=21 | | 2(h+2)+2=8 | | (4x-5)(x+4)+20=0 | | 21+2y-3=11y-10-5y | | 3t+2b=12.5 | | 8y+8y-3-5y= | | -4x+2(-6x-8)=176 | | -4(d-20)=16 | | 12x+4-x+14= | | -8(n+3)+28=-5n-11 | | -2x-7(2x-17)=-57 | | 29x+52.2=239 | | 4(k-18)-2=6 | | Y=log[4](-4y) | | 2x-7(2x-17)=-57 | | 11m-12=4m-4 |